Persistent penile frenulum in a boar and its management - GHOSH, S K (The Indian Journal of Animal Reproduction, 2005)
A crossbred boar of 11 months old was having a congenital defect of persistent penile frenulum, a band of tissue, andthereby could not copulate. Two separate frenulums ·were present. the ability of mating was restored by a simple operation of cuttingthe frenulum.
Keywords: Boar; persistent penile frenulum; congenital anomaly